2009
DOI: 10.2140/gt.2009.13.1043
|View full text |Cite
|
Sign up to set email alerts
|

Residual finiteness, QCERF and fillings of hyperbolic groups

Abstract: We prove that if every hyperbolic group is residually finite, then every quasi-convex subgroup of every hyperbolic group is separable. The main tool is relatively hyperbolic Dehn filling. Contents 1. The cusped space of a relatively hyperbolic group 3 2. Filling hyperbolic and relatively hyperbolic groups 5 3. Quasi-convexity 7 3.1. Induced peripheral structures 8 4. Proof of Theorem 0.6 11 4.1. Projections of geodesics to cusped spaces of quotients 11 4.2. The image of H is quasi-convex 14 4.3. Keeping g out … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(82 citation statements)
references
References 18 publications
2
80
0
Order By: Relevance
“…Fully quasiconvex subgroups appear in the work of F. Dahmani [14] where it is shown that, under some hypothesis, the combination of relatively hyperbolic groups along fully quasiconvex subgroups is a relatively hyperbolic group.This class of subgroups also appeared in the the work by J. Manning and the author [22] to prove a consequence of the hypothetical absence of non-residually finite hyperbolic groups that was conjectured by I. Agol, D. Groves and J. Manning [1].…”
Section: Sample Applicationsmentioning
confidence: 71%
“…Fully quasiconvex subgroups appear in the work of F. Dahmani [14] where it is shown that, under some hypothesis, the combination of relatively hyperbolic groups along fully quasiconvex subgroups is a relatively hyperbolic group.This class of subgroups also appeared in the the work by J. Manning and the author [22] to prove a consequence of the hypothetical absence of non-residually finite hyperbolic groups that was conjectured by I. Agol, D. Groves and J. Manning [1].…”
Section: Sample Applicationsmentioning
confidence: 71%
“…We will also need to make use of a relatively hyperbolic extension of the results of Agol, Groves and Manning from [AGM08].…”
Section: Malnormality In the Relative Casementioning
confidence: 99%
“…If G is a hyperbolic 3-manifold group, then Agol's Virtual Fibering theorem in [AGM12] says that G has a subgroup of finite index which fibers over the circle. Hence the result of Section 3 implies that such a subgroup is COL 2 .…”
Section: Proofmentioning
confidence: 99%